Performance and physiological quality of Escallonia resinosa seeds: prospects for their use in reforestation and restoration - Huayta Hinojosa, Luis David; Nolasco Lozano, Emily Gisella Ninfa; Guerra, Damaris; Hermoza Gamboa, Joel; Quispe Melgar, Harold Rusbelth (John Wiley and Sons Inc, 2023)
In the Andes, many native forest species are not used in reforestation or restoration programs mainly due to a lack of information about their propagation. In this study, we evaluated the performance of the seeds of Escallonia resinosa by analyzing fruit and seed productivity and characteristics, seed physiological quality, and the germination rate of seeds collected at different stages of fruit physiological maturity, using tetrazolium and standard germination tests. Our results show an estimated production (mean ± SD) of 34,252.5 ± 25,900 fruits per tree and 26.5 ± 20 million seeds per tree. Seed length was 1.0 ± 0.13 mm and seed weight was 12.4 ± 1 μg. We recognized two different morphological types of seeds: Type I seeds (lacking testa) were unviable, whereas all Type II seeds (with testa) germinated. Seed viability and germination rates were 10.5 and 48.6%, respectively; therefore, the viability test underestimated the actual germination rate. Morphological or microsite variables of the parent tree did not influence seed viability or germination. Germination rates were highest (41.8 ± 2.5%) for the seeds of fruits harvested at the initial maturity stage (green fruits). Our results show that E. resinosa is a species with potential for reforestation and restoration projects in the Andes: it has high seed production and good germination performance, and seeds can be harvested from fruits collected at different stages of physiological maturity.